Issue 25, Editorial - a LEAP and a step towards Open Access - Judith Winters (Internet Archaeology, 2009)
This issue saw yet another wide spread of content ranging from field survey results from work in southern Burgundy which cast light on the nature of Iron Age and Gallo-Roman settlement there, unusually to what has not been found from pollen work in Spain, to highlighting an online project that aims to teach archaeologists about soils, to a large monograph-style publication that looks at the national picture and nature of portable antiquities (metal-detecting) data and the relationship between patterns of recovery and historic settlement. The issue also marks the close of the first LEAP project with the publication of the fourth exemplar on the Islamic city of Merv in Turkmenistan but in doing so, it heralds the follow-on Mellon-funded LEAP II project.